A review of seating arrangements towards the 21st century classroom approach in schools / Norsafiah Norazman ... [et al.] - Norsafiah, Norazman; Abdul Halim, Ismail; Nor Haslina, Ja’afar; Muhamad Azry, Khoiry; Adi Irfan, Che Ani (Universiti Teknologi MARA, Perak, 2019)
This article articulates a framework suitable to use when making a decision about student seating arrangement in the classroom at school level as a research aim. The decision makers should establish what are the potential types of seating arrangement? Then evaluate them in terms of its contribution, significance, and impact to the student learning development. The problem of a seating arrangement is usually related to the seating student position selection that is usually decided by teachers or students that can freely choose their own seating. There are three (3) objectives covered in this article; objective 1: to justify the main factors influencing classroom seating arrangement at school building, objective 2: to identify the common patterns of seating arrangement applied for school level and objective 3; to determine the best practice of seating arrangement for 21st century classroom approach at school building. The article articulates a theory of seating arrangement in reference to five (5) common forms of seat arrangement, namely Traditional (columns and rows), Cluster, U-shaped, Stadium, and Runaway. The performance of students might drop especially weak students who are sitting at the back of the classroom if the students are not judiciously arranged. Thus, seating arrangements should be set properly to ensure optimal quality of learning in a classroom. The technique of comparative analysis was used in this study. The findings had shown that cluster seating arrangement is relevant with the 21st century learning approach, which provides more availability of collaborative learning, where it contributes to student-centred learning in a classroom.